ESTABLISHING ENVIRONMENTAL ACCOUNTABILITY THROUGH PUBLIC ACCOUNTING IN THE SDGs AGENDA OF THE GOVERNMENT OF MAKASSAR CITY - Hidayah, Nur; Imran, Haliah; Nirwana, Nirwana (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study aims to explore the readiness of the Makassar City Government in building environmental accountability through implementing public sector accounting within the framework of the Sustainable Development Goals (SDGs), while addressing the gap in existing studies related to environmental accounting and the SDGs. Using a qualitative case study approach, data were collected through in-depth interviews, document analysis of the 2021–2026 SDGs Regional Action Plan (RAD SDGs), and participatory observation. The findings reveal that although Makassar City has established a relatively well-structured SDGs planning framework and demonstrated initial commitment through budgeting and strategic programs, the budget allocation for environmental issues remains limited, approximately 3% compared to other sectors. This highlights a legitimacy gap between the city's green rhetoric and the actual implementation of fiscal policy. The lack of community and external stakeholder involvement hinders participatory and sustainable governance. This study recommends the integration of environmental accounting into public decision-making and strengthening substantive accountability principles to address transparency and legitimacy challenges in local SDG implementation.